2021
DOI: 10.3389/fnbeh.2021.672628
|View full text |Cite
|
Sign up to set email alerts
|

Second-Order Conditioning in Humans

Abstract: In contrast to the large body of work demonstrating second-order conditioning (SOC) in non-human animals, the evidence for SOC in humans is scant. In this review, I examine the existing literature and suggest theoretical and procedural explanations for why SOC has been so elusive in humans. In particular, I discuss potential interactions with conditioned inhibition, whether SOC is rational, and propose critical parameters needed to obtain the effect. I conclude that SOC is a real but difficult phenomenon to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…On the other hand, the infralimbic subregion (see Figure 5, panels A.I and B.I) has been found to participate in inhibitory learning in the aversive domain, which has been repeatedly demonstrated using extinction procedures (Burgos-Robles et al, 2007;Milad & Quirk, 2002;Milad et al, 2004;Mueller et al, 2008;Quirk et al, 2000; for reviews and interpretations of conflicting results, see Giustino & Maren, 2015;. Along the same line, a recent study by Fam et al (2022) showed that inhibitory learning (and its expression) inevitably arising in second-order fear conditioning (see Lee, 2021) is impaired when silencing the infralimbic prefrontal cortex in rats. Furthermore, inactivation of the infralimbic portion of the prefrontal cortex in rats facilitates inhibitory learning from an extinction procedure in the appetitive domain (Lay et al, 2019).…”
Section: Neurobiological Underpinnings Of Inhibitory Learningmentioning
confidence: 83%
“…On the other hand, the infralimbic subregion (see Figure 5, panels A.I and B.I) has been found to participate in inhibitory learning in the aversive domain, which has been repeatedly demonstrated using extinction procedures (Burgos-Robles et al, 2007;Milad & Quirk, 2002;Milad et al, 2004;Mueller et al, 2008;Quirk et al, 2000; for reviews and interpretations of conflicting results, see Giustino & Maren, 2015;. Along the same line, a recent study by Fam et al (2022) showed that inhibitory learning (and its expression) inevitably arising in second-order fear conditioning (see Lee, 2021) is impaired when silencing the infralimbic prefrontal cortex in rats. Furthermore, inactivation of the infralimbic portion of the prefrontal cortex in rats facilitates inhibitory learning from an extinction procedure in the appetitive domain (Lay et al, 2019).…”
Section: Neurobiological Underpinnings Of Inhibitory Learningmentioning
confidence: 83%
“…On the other hand, the infralimbic subregion (see Figure 5, Panels A.I and B.I) has been found to participate in inhibitory learning in the aversive domain, which has been repeatedly demonstrated using extinction procedures (Burgos-Robles et al, 2007; Milad & Quirk, 2002; Milad et al, 2004; Mueller et al, 2008; Quirk et al, 2000; for reviews and interpretations of conflicting results, see Giustino & Maren, 2015; Quirk & Mueller, 2008). Along the same line, a recent study by Fam et al (2022) showed that inhibitory learning (and its expression) inevitably arising in second-order fear conditioning (see Lee, 2021) is impaired when silencing the infralimbic prefrontal cortex in rats. Furthermore, inactivation of the infralimbic portion of the prefrontal cortex in rats facilitates inhibitory learning from an extinction procedure in the appetitive domain (Lay et al, 2019).…”
Section: Inhibitory Learning: the Process(es) By Which Experience Lea...mentioning
confidence: 87%
“…In other words, the HO was presented when participants expected the US to appear and this may have contributed to the persistence of higher-order associations. While several human higher-order conditioning studies use classical Pavlovian training procedures in which HO predicts a previously conditioned CS (see Lee, 2021 for review), different conditioning procedures have been used including sequential conditioning where distal (HO) and proximal (CS) both precede the US (Seymour et al, 2004;Pauli et al, 2019) and also different combinations of backward conditioning as in our study (Prével et al, 2016(Prével et al, , 2019. Higher-order learning in our paradigm was modeled after an animal higher-order conditioning study that used the same presentation structure (Gilboa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hebscher et al, 2019). However, relatively few studies have investigated higher-order conditioning in humans (Pauli et al, 2019;Prével et al, 2019;Luettgau et al, 2021;see Honey and Dwyer, 2021;Lee, 2021 for a review). Even fewer have examined the neural processes of firstorder and higher-order learning in humans.…”
Section: Introductionmentioning
confidence: 99%